January Effect Phenomenon on the Indonesian Stock Exchange, America, Germany, Japan, and China for the Period 2019-2023 - Ulfarizty, Zahra Putri; Rasulun, Astriati Baso (Journal of Advances in Accounting, Economics, and Management, 2025)
There are many factors that can affect stock price movements in the capital market. These factors can be used as a reference by investors in making investment decisions. One of them is Market Anomaly. Based on existing anomalies, seasonal anomalies are the most frequently studied anomalies in their influence on company stock returns and one of the categories of seasonal anomalies is the January Effect. This study aims to determine the January Effect phenomenon on the Indonesian, American, German, Japanese and Chinese Stock Exchanges before and after Covid-19 (2019-2023 period). In addition, to find out whether there is a difference in stock returns between January and other months, and to find out whether there is a difference in stock returns on the Indonesian, American, German, Japanese and Chinese stock exchanges during the study period. The data used is the daily main stock price index data from January 2019 to December 2023. The research method used is the comparative method and event study. Previous research results in 2019-2021 showed that there was no January effect on the Indonesian, American, German and Japanese Stock Exchanges because there was no significant difference in the average value of stock returns between January and other months. Furthermore, more in-depth research will be conducted to test whether there is an anomalous January Effect phenomenon on the Indonesian, American, German, Japanese and Chinese Stock Exchanges after the Covid-19 pandemic (case study in the 2022-2023 period)